PENERAPAN PENDEKATAN SAINTIFIK DENGAN MEDIA BENDA KONKRET TENTANG SIFAT-SIFAT BANGUN RUANG DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA PADA SISWA KELAS V SD NEGERI 4 KUWAYUHAN TAHUN AJARAN 2016/2017 - Setiadi, Ilhami Tri; Joharman, Joharman; Suripto, Suripto (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Scientific Approach using Concrete Media in Improving the Study of Mathematics about the Characteristics of Geometry for Fourth Grade Students of SD Negeri 4 Kawayuhan in the Academic Year of 2016/2017. The objectives of this research are: (1) to describe the steps on the use of scientific approach using concrete media, (2) to improve the study of mathematics about about the characteristics of geometry using concrete media, (3) to describe problems and solutions on the use of scientific approach using concrete media in improving the study of Mathematics about the characteristics of geometry for fourth This research is a collaborative classroom action research (CAR) conducted in two cycles, Subjects of this research were teacher and fourth grade students of SD Negeri 4 Kawayuhan in the academic year of 2016/2017. The conclusion of this research is the use of scientific approach using concrete media can improve the study of mathematics about about the characteristics of geometry for fourth grade students of SD Negeri 4 Kawayuhan in the academic year of 2016/2017.Keywords: scientific approach, concrete media, mathematics Abstrak: Penerapan Pendekatan Saintifik dengan Media Benda Konkret tentang Sifat-Sifat Bangun Ruang dalam Peningkatan Pembelajaran Matematika pada Siswa Kelas V SD Negeri 4 Kuwayuhan Tahun Ajaran 2016/2017. Tujuan penelitian ini yaitu: (1) mendiskripsikan penerapan pendekatan saintifik dengan media benda konkret, (2) meningkatkan pembelajaran Matematika tentang sifat-sifat bangun ruang melalui pendekatan saintifik dengan media benda konkret, (3) mendiskripsikan kendala dan solusi penerapan pendekatan saintifik dengan media benda konkret tentang sifat-sifat bangun ruang dalam peningkatan pembelajaran Matematika pada siswa kelas V SDN 4 Kuwayuhan Tahun Ajaran 2016/2017. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam 2 siklus, Subjek penelitian adalah guru dan siswa kelas V SDN 4 Kuwayuhan tahun ajaran 2016/2017. Kesimpulan penelitian ini adalah penerapan pendekatan saintifik dengan media benda konkret dapat meningkatkan pembelajaran Matematika siswa kelas V SDN 4 Kuwayuhan Tahun Ajaran 2016/2017.Kata kunci: pendekatan saintifik, media benda konkret, pembelajaran Matematika